(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the current status and the impact of a short-term educational intervention on the knowledge, attitudes, and practices of nurses in anaphylaxis management at the Emergency Department of the 108 Military Central Hospital in Vietnam. Methods: A descriptive pre - post intervention study was conducted on 201 nurses using a structured questionnaire. Data were analyzed with SPSS 20.0. Results: Prior to the intervention, 65.2% of nurses had good knowledge, 85.6% demonstrated appropriate practices, and over 80% expressed positive attitudes. However, specific gaps remained in recognizing anaphylaxis symptoms, identifying proper intramuscular injection sites, and understanding correct dosing of Adrenaline. After the intervention, the proportion of nurses with good knowledge increased to 87.6% (p = 0.005), correct anaphylaxis management practices rose from 78.1% to 88.6% (p = 0.002), correct identification of injection sites improved from 76.1% to 91% (p = 0.001), and overall good practice rate reached 94% (p = 0.03). Additionally, 100% of participants reported feeling confident in managing anaphylaxis, with over 90% strongly agreeing with statements reflecting proactive attitudes. Conclusion: The brief educational intervention significantly improved nurses’ knowledge, attitudes, and practices in anaphylaxis management, highlighting its practical value in enhancing emergency care capacity in tertiary hospitals.